Data used in "Surface Passivation Provided By An Alneal Through SiO2/TiO2 Bilayer" - Collett, K; Bonilla, R; Wilshaw, P; Cryson, M (University of Oxford, 2016)
Lifetime files taken using Sinton Lifetime Tester Data taken 2015/2016